Mesenteric panniculitis is associated with cardiovascular risk-factors: A case-control study. Issue 12 (December 2022) - Schweistein, Hagai; Weintraub, Yoav; Hornik-Lurie, Tzipi; Haskiya, Hassan; Levin, Shai; Ringel, Yehuda; Naftali, Timna
Abstract: Background: This study evaluated the prevalence of cardiovascular risk-factors in patients with mesenteric panniculitis. Aims: To determine whether cardiovascular risk-factors and mesenteric panniculitis are associated. Methods: Retrospective, matched case-control study of patients referred to Meir Medical Center, Israel, 2014–2019, who underwent computerized tomography scan, were diagnosed mesenteric panniculitis by radiologic criteria. They were compared to two, matched case-control groups: hospitalized patients without mesenteric panniculitis and the general population based on Israeli Ministry of Health surveys. Patients with active malignancy, IBD or significant intra-abdominal morbidity were excluded. Results: Of 376 patients with mesenteric panniculitis diagnosed by computerized tomography, 187 were included. Compared to hospital patients, they had higher incidence of dyslipidemia (77.5%/56.7%), hypertension (52.4%/40.6%), obesity (body mass index>30) (60.4%/30.5%) and nonalcoholic fatty liver disease (42.2%/16.6%). Similar differences were observed compared to the general population. In multivariable logistic regression, dyslipidemia, obesity, and nonalcoholic fatty liver disease were independent predictors for mesenteric panniculitis. Conclusions: Patients with mesenteric panniculitis have more cardiovascular risk-factors compared to a case-control group and to the general population. This suggests that mesenteric panniculitis is clinically significant and may be part of the metabolic morbidity burden. This association should be further explored.